2002
DOI: 10.1177/0022022102033003005
|View full text |Cite
|
Sign up to set email alerts
|

Social Axioms

Abstract: Downloaded from JOURNAL OF CROSS-CULTURAL PSYCHOLOGY Leung et al. / SOCIAL AXIOMSTo broaden our conceptual framework for understanding cultural differences, the present article reports two studies that examined whether pancultural dimensions based on general beliefs, or social axioms, can be identified in persons from five cultures. A Social Axioms Survey was constructed, based on both previous psychological research primarily in Europe and North America on beliefs and qualitative research conducted in Hong Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(106 citation statements)
references
References 26 publications
2
94
0
10
Order By: Relevance
“…This construct consists of two dimensions: fate determinism (e.g., "Fate determines one's success and failure") and fate alterability (e.g., "There are certain ways for people to improve their destiny"). Fate control has been used as a single construct (Leung et al, 2002;Safdar et al, 2006) and confirmatory factor analysis in this study found that the single-factor model showed a better fit than the two-factor model. Cronbach's α was .84 in the present study.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…This construct consists of two dimensions: fate determinism (e.g., "Fate determines one's success and failure") and fate alterability (e.g., "There are certain ways for people to improve their destiny"). Fate control has been used as a single construct (Leung et al, 2002;Safdar et al, 2006) and confirmatory factor analysis in this study found that the single-factor model showed a better fit than the two-factor model. Cronbach's α was .84 in the present study.…”
Section: Methodsmentioning
confidence: 78%
“…Fate control was measured using the eight-item "fate control" subscale of the Social Axioms Scale (Leung et al, 2002;Safdar, Lewis, & Daneshpour, 2006). This construct consists of two dimensions: fate determinism (e.g., "Fate determines one's success and failure") and fate alterability (e.g., "There are certain ways for people to improve their destiny").…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, text and audio materials were prepared using the Social Axioms Survey (Leung et al, 2002) items for the control conditions; sample items include 'Human behaviour changes with the social context' and 'Most disasters can be predicted'. The Social Axioms Survey was chosen as control material because the measure focuses on people's general beliefs about the world rather than self-related perception (Leung et al, 2002). The Chinese version of the Social Axioms Survey items was used.…”
Section: Methodsmentioning
confidence: 99%
“…The horizontal dimension embodies a concern with social justice, charity toward fellow human beings, and serving humanity in mercy and justice. Religiosity refers to an axiomatic belief in a supernatural power and its positive benefits to people's lives (Leung et al, 2002). We proposed the following hypotheses:…”
Section: Predictors Of Edrsmentioning
confidence: 99%